ANALISIS YURIDIS PEMBUKTIAN TINDAK PIDANA DEEPFAKE PORN YANG TERJADI AKIBAT PEMANFAATAN ATAU PENYALAHGUNAAN ARTIFICAL INTELIGENCE (AI) - Muhammad As Ari. Arief Mamba (Qistie Jurnal Ilmu Hukum, 2026)
Artificial intelligence is currently being massively misused by cybercriminals. Deepfake or audio/video impersonation is often used as a means to create manipulated videos with pornographic content. The purpose of this research is to understand the legal proof of criminal acts related to the misuse of Artificial Intelligence (AI) Deepfake Porn according to the positive legal system in Indonesia, as well as the legal protection for victims of such misuse under the positive legal system in Indonesia. The research method used in this thesis is normative legal research, employing both a statute approach and a conceptual approach. The research results indicate that according to Article 183 of the Criminal Procedure Code, at least two valid pieces of evidence and the judge's conviction are required to convict the defendant. Deepfake pornography, as a violation of digital privacy, demands proof through digital forensics. According to Article 5 paragraphs (1) and (2) of Law No. 1 of 2024, electronic content resulting from Deepfake is deemed valid evidence in court. Therefore, proving the ownership of the accounts used in the creation and distribution of Deepfake content is very important, because without this, the criminal elements in the indictment are not considered fulfilled. And legal protection for victims of abuse of Deepfake Artificial Intelligence technology includes: preventive legal protection, repressive measures (take down and right to be forgotten), compensation, restitution, as well as handling, protection, and rehabilitation for victims of sexual violence